2015
DOI: 10.3109/13880209.2015.1080731
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of turmeric (Curcuma longa) effect on biochemical and pathological parameters of liver and kidney in chicken aflatoxicosis

Abstract: Context: Aflatoxins as potent mycotoxins can influence vital parameters in chickens. Turmeric was used in decreasing toxic effect of mycotoxins on vital organs, traditionally. Objective: The study compared the protective effect of turmeric and Mycoad TR in broilers exposed to aflatoxin. Materials and methods: Chickens (270) were divided into six groups. The chickens were fed a basal diet, turmeric extract (5 mg/kg diet), Mycoad TR (25 mg/kg diet), productive aflatoxin (3 mg/kg diet), aflatoxin plus turmeric ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 36 publications
3
32
0
Order By: Relevance
“…Histopathologically, supplementation of 100 ppb aflatoxin in G4 which had severe liver and kidney lesions as indicative for aflatoxicosis exhibited through hemorrhage and focal hepatic necrosis with inflammatory cell infiltration and fatty degeneration of hepatocytes which may be due to disturbance of oxidant/antioxidant balance system and kidney as congestion of renal blood vessels, interstitial nephritis with mononuclear cell infiltrations. Also, previous researches which recorded the toxic effect of aflatoxins in liver (Gholami-Ahangaran et al, 2016 andTessari et al, 2006) and kidney (Mohamed and Mohamed, 2009). The inclusion of DPS to diet contains 100 ppb AF as in G6 and G7 reduced the severity of pathological changes.…”
Section: Discussionmentioning
confidence: 94%
“…Histopathologically, supplementation of 100 ppb aflatoxin in G4 which had severe liver and kidney lesions as indicative for aflatoxicosis exhibited through hemorrhage and focal hepatic necrosis with inflammatory cell infiltration and fatty degeneration of hepatocytes which may be due to disturbance of oxidant/antioxidant balance system and kidney as congestion of renal blood vessels, interstitial nephritis with mononuclear cell infiltrations. Also, previous researches which recorded the toxic effect of aflatoxins in liver (Gholami-Ahangaran et al, 2016 andTessari et al, 2006) and kidney (Mohamed and Mohamed, 2009). The inclusion of DPS to diet contains 100 ppb AF as in G6 and G7 reduced the severity of pathological changes.…”
Section: Discussionmentioning
confidence: 94%
“…The biochemical alterations during aflatoxicosis can be attributed to liver injuries (Kubena et al, 1993;Shi et al, 2006). Liver injuries are responsible for changes in serum indices (Gholami-Ahangaran et al, 2016). The increased activities of these enzymes in chickens treated with diets contaminated with aflatoxins can be attributed to liver damage and enzyme leakage into the blood vessels (Gholami-Ahangaran et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Liver injuries are responsible for changes in serum indices (Gholami-Ahangaran et al, 2016). The increased activities of these enzymes in chickens treated with diets contaminated with aflatoxins can be attributed to liver damage and enzyme leakage into the blood vessels (Gholami-Ahangaran et al, 2016). Gowda et al (2008) also reported that liver damage is responsible in increasing the activities of liver enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…The liver is the primary target organ for AF. Long-term intake of feeds contaminated with AF results in negative effects on the liver, such as hepatic cell and tissue injury, as well as gross and microscopic abnormalities ( Williams et al., 2011 , Gholami-Ahangaran et al., 2016 ). In classical epidemiology, researchers revealed the relationship between AF exposure and high prevalence of human liver cancer in various areas of Asia and Africa ( Pitt, 2000 ).…”
Section: Introductionmentioning
confidence: 99%